2013
DOI: 10.1016/j.jacc.2013.02.060
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Bileaflet Mitral Valve Prolapse Syndrome in Patients With Otherwise Idiopathic Out-of-Hospital Cardiac Arrest

Abstract: The authors describe a "malignant" subset of patients with MVP who experienced life-threatening ventricular arrhythmias. This phenotype is characterized by bileaflet MVP, female sex, and frequent complex ventricular ectopic activity, including premature ventricular contractions of the outflow tract alternating with papillary muscle or fascicular origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
317
2
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(346 citation statements)
references
References 44 publications
14
317
2
4
Order By: Relevance
“…The malignant "phenotype" is characterized by young women with bileaflet MVP, biphasic or inverted T waves in the inferior leads, and frequent complex ventricular ectopic activity with documented ventricular bigeminy or ventricular tachycardia (VT) and PVC configurations of outflow tract alternating with papillary muscle or fascicular origin (15)(16)(17).…”
Section: Causes Of Scdmentioning
confidence: 99%
See 1 more Smart Citation
“…The malignant "phenotype" is characterized by young women with bileaflet MVP, biphasic or inverted T waves in the inferior leads, and frequent complex ventricular ectopic activity with documented ventricular bigeminy or ventricular tachycardia (VT) and PVC configurations of outflow tract alternating with papillary muscle or fascicular origin (15)(16)(17).…”
Section: Causes Of Scdmentioning
confidence: 99%
“…This type is linked to fibrosis of the basal interventricular septum in MVP cases (23). Table 1 summarizes the mechanisms of SCD in MVP patients (1,8,10,(15)(16)(17).…”
Section: Causes Of Scdmentioning
confidence: 99%
“…38 Mitral valve prolapse in female patients with ECG repolarisation abnormalities, and frequent complex ventricular ectopy, has also been associated with out-of-hospital cardiac arrest. 39,40 An association between air pollution (fine particulate matter with an aerodynamic diameter <2.5 µm and ozone) and out-of-hospital cardiac arrest has recently been demonstrated. 41 SCDs account for most cardiac and many non-AIDS-related natural deaths in HIV-infected patients.…”
Section: Department Of Defense Cardiovascular Death Registry In the Umentioning
confidence: 99%
“…Accordingly, a malignant MVP subgroup was characterized as young women with bileaflet MVP, and frequent complex ventricular ectopy. Importantly, the complex ventricular ectopy was characterized by activity originating from both LV outflow tract and LV papillary muscles [9]. Notably, bileaflet MVP by itself without the other risk profile was shown to predict a reduced risk for SCD [10].…”
mentioning
confidence: 99%
“…A review of Myo Clinic's out of hospital cardiac arrest cases including 1200 cases, revealed 24 SCD cases which were defined as idiopathic after ruling out ischemia, various cardiomyopathy or channelopathies [9]. Ten out of these 24 idiopathic SCD cases were found to have bileaflet MVP, of whom 90% were women; 80% had biphasic or inverted T waves on ECG and 100% had a significant ventricular premature activity on a Holter monitoring.…”
mentioning
confidence: 99%